Seasonal changes in the ovarian structure of the cape fur seal (Arctocephalus pusillus pusillus) - Bester, Marthan Nieuwoudt (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2006.